2013
DOI: 10.1073/pnas.1222861110
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem cell and progenitor cell mechanisms in myelodysplastic syndromes

Abstract: Myelodysplastic syndromes (MDS) are a group of disorders characterized by variable cytopenias and ineffective hematopoiesis. Hematopoietic stem cells (HSCs) and myeloid progenitors in MDS have not been extensively characterized. We transplanted purified human HSCs from MDS samples into immunodeficient mice and show that HSCs are the disease-initiating cells in MDS. We identify a recurrent loss of granulocyte-macrophage progenitors (GMPs) in the bone marrow of low risk MDS patients that can distinguish low risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
268
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(290 citation statements)
references
References 39 publications
18
268
1
3
Order By: Relevance
“…We recently showed that the HSCs in MDS that show a clonal pathogenic chromosomal event such as 5q-or monosomy 7 expand at the expense of normal HSCs, just as we had shown in CML (240). But the progeny of these hypercompetitive HSCs produce progenitors that are phagocytosed, likely to be responsible for the loss in blood of red blood cells and/or granulocytes and/or platelets (240). So MDS is a prototype of preleukemic progression wherein the successful clone has blocked programmed cell death, but its oligolineage progeny, also highly viable, can, in a stage-specific manner, express cell surface calreticulin and are phagocytosed in a calreticulin-dependent event (240).…”
Section: Cancer Stem Cells and The Therapeutics That Come From Them: mentioning
confidence: 59%
See 2 more Smart Citations
“…We recently showed that the HSCs in MDS that show a clonal pathogenic chromosomal event such as 5q-or monosomy 7 expand at the expense of normal HSCs, just as we had shown in CML (240). But the progeny of these hypercompetitive HSCs produce progenitors that are phagocytosed, likely to be responsible for the loss in blood of red blood cells and/or granulocytes and/or platelets (240). So MDS is a prototype of preleukemic progression wherein the successful clone has blocked programmed cell death, but its oligolineage progeny, also highly viable, can, in a stage-specific manner, express cell surface calreticulin and are phagocytosed in a calreticulin-dependent event (240).…”
Section: Cancer Stem Cells and The Therapeutics That Come From Them: mentioning
confidence: 59%
“…Now we knew that it was the "eat me" signal that was expressed on the surface of all AML cells. We showed later that calreticulin was expressed on the surface of the GMP and erythrocyte progenitor cells in the marrow of patients with myelodysplastic syndrome (MDS), and we showed that, as a consequence, their frequency relative to other marrow cells was significantly diminished (240). We recently showed that the HSCs in MDS that show a clonal pathogenic chromosomal event such as 5q-or monosomy 7 expand at the expense of normal HSCs, just as we had shown in CML (240).…”
Section: Cancer Stem Cells and The Therapeutics That Come From Them: mentioning
confidence: 68%
See 1 more Smart Citation
“…[1][2][3] Despite their genetic heterogeneity, they share common phenotypic features including low peripheral blood counts (cytopenias) in spite of a hypercellular bone marrow (ineffective hematopoiesis), dysplasia and a variable propensity for transformation to acute myeloid leukemia (AML). 4 Programmed cell death or apoptosis of white blood cells is a common feature, and is thought to contribute to the cytopenias particularly in early stages of the disease.…”
mentioning
confidence: 99%
“…Deren genetische Instabilität ist die Grundlage für den Erwerb einer Vielzahl weiterer Mutationen, die mit dem Verlust der normalen Differenzierungskapazität schließlich funktionell zu einer dysplastischen und ineffektiven Hämatopoese führen [2]. Allerdings findet sich in Kollektiven älterer (>70 Jahre), asymptomatischer Personen bei einem Anteil von bis zu 10 % der Nachweis einer klonal veränderten Hämatopoese, deren klinische Bedeutung gegenwärtig unklar ist [3].…”
Section: » Klinische Hauptphänomene Sind Anämie Erhöhte Blutungsbereunclassified